This is a system of linear equations. We can solve by elimination. First, we write out the two equations:
3m - 4n = 1
4m - 6n = 5
We want to make the coefficients of one of the variables the same so that we can eliminate it. Let's make the coefficient of m 12 for both equations. To do that for the first, we have to multiply both sides by 4:
12m - 16n = 4
To do that for the second, we have to multiply both sides by 3:
12m - 18n = 15
Put the two equations together:
12m - 16n = 4
12m - 18n = 15
We can subtract the bottom equation from the top and eliminate the 12m to get:
-16n - (-18n) = 4 - 15
2n = -11
n = -5.5
Now that we know n, we can solve for m. We can use one of the original equations and put in the value -5.5 for n and solve for m: 3m - 4 * (-5.5) = 1
3m + 22 = 1
m = -7
and
n = -5.5